El impacto de la realidad virtual en la narración de historias periodísticas - Dávila Alvarado, Estrella Estefania (2025)
The narrative of traditional journalism was a source and emergence of issuing information, and with it, different genres of journalistic narrative emerged, such as fiction, facts based on real stories, documentaries, informative, literary, among others that are still valid to this day; What marks this era is modernization due to its growth and innovation; Day by day we have seen how new technology spreads very quickly due to its precision and ease that makes the daily life of human beings more useful and simpler. Today something imaginable becomes a reality, converting the traditional journalistic narrative into a new personification and innovation, which together with technology, creates virtual reality with journalism narratives, this emerges new alternatives and perspectives for the audience, thus leaving a mark framed with the stories that are transmitted and narrated from the diversity of the field in which it is reported; The human being becomes more empathetic, flexible and, above all, knows more about the suffering of others, heartbreaking situations and stories, as well as new systematization of learning guides which help society progress, immersing themselves in virtual reality environments.